Aspirations of the middle class: Voting on redistribution and status concerns - Kai A. Konrad; Florian Morath (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
This paper analyzes the role of narrowly selfish and other-regarding preferences for the median voter in a Meltzer-Richard (1981) framework. We use computerized and real human co-players to distinguish between these sets of motivations. Redistribution to real co-players has a negative effect on the median voter's tax rate choice. Further, perceived income mobility decreases the desired amount of redistribution. Our results suggest the importance of concerns about own mobility as well as status concerns of the median voter who tends to keep distance to the low-income group, whereas inequity aversion does not play a role in the political economy context.
Keywords: C91; D03; D72; D78; H20; 330; Redistribution; other-regarding preferences; median voter; experiments